2014
DOI: 10.1039/c3ob42130a
|View full text |Cite
|
Sign up to set email alerts
|

Ring contraction of 1,3-diphenylbenzo[1,2,4]triazinyl radicals to 1,2-diphenylbenzimidazoles

Abstract: Reductive ring contraction of 1,3-diphenyl-1,4-dihydrobenzo[e][1,2,4]triazin-4-yls (Blatter's radicals) using zinc powder (2 equiv.) in acetic acid heated to ca. 118 °C gives 1,2-diphenylbenzimidazoles in high yield. 1,3-Diphenylbenzo[e][1,2,4]triazin-7(1H)-one and the zwitterionic tetraphenylhexaazaanthracene (TPHA) also undergo reductive ring contractions to give 1,2-diphenylbenzimidaz-6-ol and 1,2,6,7-tetraphenyl-1,7-dihydrobenzo[1,2-d:4,5-d']diimidazole, respectively. By using less zinc, the incomplete red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Blatter radical ( 1a ), also known as 1,3-diphenyl-1,4-dihydrobenzo­[ e ]­[1,2,4]­triazin-4-yl, is an air- and moisture-stable neutral organic radical, first reported in 1968, that shows reversible redox behavior (Figure ). In the presence of strongly oxidizing agents (e.g., MnO 2 or KMnO 4 ), it gives the useful benzotriazinone 2 , several analogues of which have interesting biological properties, whereas with strongly reducing agents (e.g., Zn in AcOH), it gives 1,2-diphenylbenzimidazole ( 3 ) . Aside from an extensive EPR studies by Neugebauer, and later by Kadirov, little else was reported until Wudl reignited interest by preparing a pressure-sensitive semiconducting charge transfer complex of Blatter radical 1a with 7,7,8,8-tetracyanoquinodimethane (TCNQ) and the unusual zwitterionic tetraphenyl­hexa­azaanthracene (TPHA) (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Blatter radical ( 1a ), also known as 1,3-diphenyl-1,4-dihydrobenzo­[ e ]­[1,2,4]­triazin-4-yl, is an air- and moisture-stable neutral organic radical, first reported in 1968, that shows reversible redox behavior (Figure ). In the presence of strongly oxidizing agents (e.g., MnO 2 or KMnO 4 ), it gives the useful benzotriazinone 2 , several analogues of which have interesting biological properties, whereas with strongly reducing agents (e.g., Zn in AcOH), it gives 1,2-diphenylbenzimidazole ( 3 ) . Aside from an extensive EPR studies by Neugebauer, and later by Kadirov, little else was reported until Wudl reignited interest by preparing a pressure-sensitive semiconducting charge transfer complex of Blatter radical 1a with 7,7,8,8-tetracyanoquinodimethane (TCNQ) and the unusual zwitterionic tetraphenyl­hexa­azaanthracene (TPHA) (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Koutentis and co-workers synthesized 1,3-diaryl-1,4-dihydrobenzo[e] [1,2,4]triazin-4-yls 245 via an aza-Wittig-mediated synthesis (Schemes 64 and 65). 58 [1,2,4]triazin-4-yls 245, known as Blatter radicals, are air-and moisture-stable organic compounds that can be converted into benzotriazinones 247 59 and 1,2-diphenylbenzimidazoles 246 60 in the presence of oxidizing and reducing agents, respectively (Scheme 64). Benzotriazinones 59 In 2012, Ding and co-workers reported the unexpected synthesis of 2,4,5-trisubstituted oxazoles 254 via intermolecular aza-Wittig reaction (Scheme 66).…”
Section: Tandem Intermolecular Aza-wittig/intramolecular Cyclizationmentioning
confidence: 99%
“…Imidazolo-, oxazolo-and thiazolo-fused 1,2,4-benzotriazinyls (307) all underwent zinc-mediated ring contractions to give imidazolo-, oxazolo-and thiazolo-fused benzimidazoles (314) in excellent yields (Scheme 62). 115 Scheme 62. Reductive ring contraction of TPHA (232), 1,2,4-benzotriazinone (8) and imidazolo-, oxazolo-and thiazolo-fused benzotriazinyl radicals (296).…”
Section: 24-benzotriazinyl Radicalsmentioning
confidence: 99%